Determination of mechanical properties by ultrasonic method - Sarhani, Mohamed El Said; Nouioua, Ismail (Université Amar Telidji - Laghouat - Département des sciences de la matière, 2018)
This work deals with the experimental study of some samples (Aluminum alloy, steel X52 and steel X70 ), in order to determine the mechanical properties using ultrasound. Based on the results of the simulation of the acoustic signal received by the sonic probe, we can exploit the signal obtained experimentally, using the longitudinal and transverse velocity relationships that enable it to calculate the young modulus, the shear modulus and the Poisson ratio of the studied samples.